Genetic Variability, Heritability and Relationships of Yield and Yield Contributing Characters in Introduction Kidney Beans - Yuliawati; Nani Yulianti; Raden Deti Indriani (Universitas Djuanda, 2021)
Efforts to improve the yield of kidney beans can be done through plant breeding programs, namely through introduction and selection activities. Selection is carried out to identify superior genotypes and will be effective if the relationship and influence between the characters are known. The research was conducted to study the closeness of the relationship between the characters of introduced kidney beans from Timor Leste and their direct and indirect effects through correlation and path analysis. This research was conducted at the Universitas Djuanda Experimental Garden, Ciawi, Bogor, in August-November 2020. The research design used was a randomized complete block design (RCBD) with accession as a factor and repeated 4 times. The results showed that the number of pods character had the highest correlation coefficient value on seed weight per plant as a yielding character for kidney beans with a value of r = 0.91 *. Besides, the number of pods also had a high direct (0.35) and indirect (0.91) effect through the characters of the number of seeds per pod (0.8) and the number of branches (0.3).